2020
DOI: 10.1039/c9sm02115a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the ion size on the stability of the smectic phase of ionic liquid crystals

Abstract: It takes two to tango: an experimental and computational study of ionic liquid crystals reveals the subtle balance between the energetic interactions in the hydrophobic and ionic layers that contribute to the stabilization of the ionic smectic phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…In addition to the charge strength, the surface charge density of the counterion also plays a role as suggested in a further study by Saielli, Wang and others [210] . In agreement with experimental observations, their fully atomistic MD simulations of N ‐alkyl‐3‐methylpyridinium halides show that the SmA stability increases “the stronger van der Waals interactions from the longer alkyl chains and the stronger electrostatic interactions from the smaller anions with a higher charge density”.…”
Section: Computer Simulation Of Ionic Liquid Crystalline Phasessupporting
confidence: 68%
“…In addition to the charge strength, the surface charge density of the counterion also plays a role as suggested in a further study by Saielli, Wang and others [210] . In agreement with experimental observations, their fully atomistic MD simulations of N ‐alkyl‐3‐methylpyridinium halides show that the SmA stability increases “the stronger van der Waals interactions from the longer alkyl chains and the stronger electrostatic interactions from the smaller anions with a higher charge density”.…”
Section: Computer Simulation Of Ionic Liquid Crystalline Phasessupporting
confidence: 68%
“…It is not uncommon for LC homologs to show different phase behaviour as a function of chain length [67]. Phase behaviour of ILCs is therefore determined by a critical balance between hydrophobic interactions of the alkyl chains, and ionic electrostatic interactions that depend on cation and anion structures, and this has been confirmed by recent molecular simulation [68][69][70][71][72][73][74].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 89%
“…However, when the headgroup surpasses a certain size requiring a similar volume as the hydrophobic part and provides additional polyphilic interactions, lamellar mesophases were found again (for example, 10 c ). These results are in good agreement with molecular dynamics (MD) simulations on pyridinium ILCs, which revealed that only those compounds with a relatively large volume ratio of cation to anion form stable SmA phases …”
Section: Resultsmentioning
confidence: 99%
“…These results are in good agreement with molecular dynamics (MD) simulations on pyridinium ILCs, which revealed that only those compounds with ar elatively large volume ratio of cation to anion form stable SmA phases. [69] In conclusion, aminocyclopropenium ILCs serve as welldefined model compounds to study self-assembly and nanosegregation, which are important in polyelectrolytes used for battery materials.T hese ILCs bridge the gap between low molecular weight organocatalysts and polymeric electrolytes, and thus,c ontribute to the general utility of 3-ring aromatic compounds. (9,14), guanidinium (12,13), and aminocyclopropenium (7, 10;* denotes decomposition).…”
Section: Angewandte Chemiementioning
confidence: 99%